2022
DOI: 10.3389/fmed.2022.889640
|View full text |Cite
|
Sign up to set email alerts
|

Theragnostic 64Cu/67Cu Radioisotopes Production With RFT-30 Cyclotron

Abstract: 64Cu and 67Cu are theragnostic pair radionuclides with promising application in the nuclear medicine. 64Cu is PET nuclide for the non-invasive diagnosis and 67Cu is beta emitter for therapy of various cancers. This study discusses optimization efforts in the production of these radioactive coppers carried out with 30 MeV cyclotron. Optimized conditions include target preparation, chemical separation, and quality control. The production routes of 64Cu and 67Cu were studied based on the nuclear reactions of 64Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The radionuclide content of the produced [ 67 Cu]CuCl 2 solution is characterized by gamma spectroscopy, quantifying a RNP of 99.5%, with radionuclide impurities consisting of 64 Cu (0.3%), 61 Cu (0.03%), 67 Ga (0.1%) and 66 Ga (0.05%), comparable to previously published results [22]. It is worthwhile mentioning that the 67 Ga content is estimated from the detected 66 Ga activity, since both 67 Cu and 67 Ga share the same gamma lines only with different intensities, making it nearly impossible to directly quantify the gallium-67 impurities.…”
Section: [ 67 Cu]cucl 2 Productionsupporting
confidence: 84%
“…The radionuclide content of the produced [ 67 Cu]CuCl 2 solution is characterized by gamma spectroscopy, quantifying a RNP of 99.5%, with radionuclide impurities consisting of 64 Cu (0.3%), 61 Cu (0.03%), 67 Ga (0.1%) and 66 Ga (0.05%), comparable to previously published results [22]. It is worthwhile mentioning that the 67 Ga content is estimated from the detected 66 Ga activity, since both 67 Cu and 67 Ga share the same gamma lines only with different intensities, making it nearly impossible to directly quantify the gallium-67 impurities.…”
Section: [ 67 Cu]cucl 2 Productionsupporting
confidence: 84%
“…Later on, Jamriska et al [ 36 ] and Kastleiner et al [ 27 ] showed consistent results. With a rather low cross-section (15 mb at max), only Cu activities of up to 700 have been reported through this reaction so far [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radioconjugates for Targeted PET, PET/MR, and PET/NIRF Imaging of PCa NP-based radioconjugates for PET and PET/MR imaging of PCa have been focused on five positron-emitting radionuclides: 64 Cu, 68 Ga, 18 F, 124 I, and 89 Zr. Among them, 64 Cu was the most frequently used for radiolabelling of NPs due to its attractive nuclear properties [85][86][87]. The characteristics of 64 Cu and other radionuclides are presented in Table 2.…”
Section: Nanoparticle-basedmentioning
confidence: 99%